Leaf nodule symbiosis: function and transmission of obligate bacterial endophytes. (August 2018) - Pinto-Carbó, Marta; Gademann, Karl; Eberl, Leo; Carlier, Aurelien
Graphical abstract: Highlights: Plants of diverse lineages form intimate symbioses with bacteria in leaves. Leaf nodule symbionts colonize the seeds and are vertically-transmitted. Leaf nodule bacteria contribute secondary metabolites active against herbivores. Reduced genomes highlight functions required for a strictly endophytic lifestyle. Abstract : Various plant species establish intimate symbioses with bacteria within their aerial organs. The bacteria are contained within nodules or glands often present in distinctive patterns on the leaves, and have been used as taxonomic marker since the early 20th century. These structures are present in very diverse taxa, including dicots (Rubiaceae and Primulaceae) and monocots ( Dioscorea ). The symbionts colonize the plants throughout their life cycles and contribute bioactive secondary metabolites to the association. In this review, we present recent progress in the understanding of these plant–bacteria symbioses, including the modes of transmission, distribution and roles of the symbionts.